Sustainable revitalization's theory evolution: evaluating revitalization attributes / Prof. Dr. Dasimah Omar, Assoc. Prof. Dr. Rodzyah Mohd Yunus and Zalina Samadi - Omar, Dasimah; Mohd Yunus, Rodzyah; Samadi, Zalina (Research Management Institute (RMI), 2011)
There were 911 sites including 704 cultural, 180 natural, 27 mixed properties were included as outstanding universal value by the UNESCO World Heritage Convention in June 2010. Malaysian heritage sites were Melaka and Georgetown as listed since 2007. However, World Heritage Lists is not an ultimate benchmark to qualify heritage site rated which considered as high revitalization. Of course, there are multi-ways to evaluate heritage streets prior to an establishment of a street as so called as "Great Heritage Streets". There are streets which are very outstanding and famous streets such as Oxford Streets in London,United Kingdom; Orchard Street in Singapore; Ista'lal Street in Istanbul, Turkey and Petaling Street in Kuala Lumpur, Malaysia. According to (Krier, 1979), he defines streets as urban space for public besides square. Marcus C.C. Francis, C (1998) research had highlighted on the importance of Physical Attributes (PA) and Spiritual Attributes (SA) in revitalizing street in order for developing a creative street and hence enliven the urban space.ln the practice of urban heritage conservation and revitalization, multi role-players and disciplinarians involves in the transformation of an urban heritage streets. The street by all mean is made up of three dimensional components of architectural heritage building as its main physical component, street system as the link and street shopping as the business operation. The main vertical components of shop houses are fagade and window display. Regardless its impressively charming character, the locality of the shop houses has substantial influence. For instance the urban and heritage contextual guidelines are the existing setting for shop houses in Georgetown and Malacca. The shop owners in both locations are complying with the city manager's commercial and heritage buildings guidelines. Functionally mixed-used for shopping, working and living but personalization is the expected quality by end users. This high expectation on heritage enhancement however has caused heritage shop owners to a new pressure. They are in the critical position in maintaining both heritage aesthetic and economical balance. The heritage shop owners in heritage streets are either passive spectators or actively involved in a heritage community participation in business activities on their profit-making policy. On the other hand urban managers were managing the city vision and occupied their financial management and incentives for heritage owners for conserving their heritage property in order to increase the city's revenue. Many researches were conducted on urban design in designing the outdoor urban spaces but on the other hand had an acute interest on evaluating heritage observer's perception. Thus, this research explored physical attributes from end-users' perception with high heritage awareness in mind and soul. Hopefully by end of the research, the findings on physical and spiritual attributes will improve the sustainable revitalization theory.